2019
DOI: 10.1039/c8cc09696a
|View full text |Cite
|
Sign up to set email alerts
|

The chiral interfaces fabricated by d/l-alanine-pillar[5]arenes for selectively adsorbing ctDNA

Abstract: In this paper, the d/l-AP5-interfaces are firstly fabricated by attaching d-alanine-pillar[5]arene and l-alanine-pillar[5]arene (d/l-AP5) onto the gold surface, and they exhibit a significantly different chiral influence on the morphology and the adsorption quantity of the adsorbed ctDNA molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…We have demonstrated that the chirality of pillar[n]arene derivatives could be manipulated by external stimuli, including temperature, redox, light, and pressure ( Yao et al, 2017 ; Xiao et al, 2020 ; Yao et al, 2021a ; Yao et al, 2021b ). The synthetic approaches for obtaining chiral pillar[5]arenes include introducing chiral or bulky groups on the openings, fusing a side ring onto one subunit, or threading with an axle to block the interconversion between S p and R p conformers ( Ogoshi et al, 2011 ; Chen et al, 2013 ; Strutt et al, 2014b ; Shurpik et al, 2016 ; Li Q. et al, 2019 ; Ma et al, 2019 ; Zhang et al, 2019 ). However, pillar[5]arenes’ planar-chiral S p and R p enantiomers need to be separated by HPLC enantio-resolution of the racemic mixture to study their chiroptical properties.…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated that the chirality of pillar[n]arene derivatives could be manipulated by external stimuli, including temperature, redox, light, and pressure ( Yao et al, 2017 ; Xiao et al, 2020 ; Yao et al, 2021a ; Yao et al, 2021b ). The synthetic approaches for obtaining chiral pillar[5]arenes include introducing chiral or bulky groups on the openings, fusing a side ring onto one subunit, or threading with an axle to block the interconversion between S p and R p conformers ( Ogoshi et al, 2011 ; Chen et al, 2013 ; Strutt et al, 2014b ; Shurpik et al, 2016 ; Li Q. et al, 2019 ; Ma et al, 2019 ; Zhang et al, 2019 ). However, pillar[5]arenes’ planar-chiral S p and R p enantiomers need to be separated by HPLC enantio-resolution of the racemic mixture to study their chiroptical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Amino acids are the main building blocks of many enzymes, proteins and peptides, and play important role in metabolic processes. Consequently, functionalization of macrocyclic compounds by amino acid fragments allows the creation of derivatives with antimicrobial activity, use them as artificial ion channels, for targeted drug delivery, or as cholinesterase inhibitors [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 36 , 37 ]. In this regard, the design of synthetic macrocyclic receptors containing amino acid residues is fascinating task for modern organic and supramolecular chemistry.…”
Section: Resultsmentioning
confidence: 99%
“…Introduction of chiral amino acid fragments into the macrocycle’s structure makes it possible to create novel water-soluble receptors based on them. A number of pillararenes containing alanine (Ala) [ 24 , 25 , 26 ], phenylalanine (Phe) [ 27 ], arginine (Arg) [ 28 ], tryptophan (Trp) [ 29 ], glycine (Gly) [ 30 , 31 ] and diglycine (Gly-Gly) [ 32 ] fragments have been reported in the literature. These compounds have been applied in various fields: from the binding of alkali metal cations and dyes to targeted drug delivery and use as ion channels.…”
Section: Introductionmentioning
confidence: 99%
“…The kinetic adsorption process of lysozyme was studied through Electrochemical Impedance Spectroscopy. The adsorption of lysozyme can hinder the electron transfer at the gold interface, and the higher the adsorption amount, the larger the impedance . Therefore, the kinetic adsorption process of lysozyme can be studied through EIS.…”
Section: Figurementioning
confidence: 99%
“…The adsorption of lysozyme can hinder the electron transfer at the gold interface, and the higher the adsorption amount, the larger the impedance. [15] Therefore, the kinetic adsorption process of lysozyme can be studied through EIS. As shown in Figure 4a, the impedance of all interfaces increases with the increase of Figure 3.…”
mentioning
confidence: 99%